The effect of the group to group exchange method on high school students' learning outcomes on environmental change materials - Sintia Ariska Putri; Ulfayani Mayasari (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
The low ability of student learning outcomes is because teachers never manipulate the ability of learning outcomes, and many teachers still use conventional learning approaches. The purpose of this study was to determine whether the Group To Group Exchange method has no effect on student learning outcomes on environmental change in one of the Islamic high schools in Medan. This research is a quasi-experimental study with a Nonequivalent pretest-posttest control group design. Data analysis of student learning outcomes used the ttest formula, with the help of SPSS version 25 data processing. Data analysis of student learning outcomes by calculating the average learning outcomes showed that the experimental class using the Group to Group Exchange method was higher than the control class. The prerequisite test proved that the data were normally distributed and homogeneous. The results of the calculation of the ttest test show that tcount is higher than ttable, so there is an influence so that it shows tcount > ttable then Ha2 is accepted. The results of this study indicate that there are influences and differences before and after the application of the Group to Group Exchange method on student learning outcomes on environmental change material in one of the Islamic high schools in Medan so that the findings obtained can be applied by teachers in carrying out learning, especially biology subjects.Abstrak Rendahnya kemampuan hasil belajar siswa disebabkan guru tidak pernah memperdayakan kemampuan hasil belajar dan masih banyak guru yang menggunakan pendekatan pembelajaran konvensional. Tujuan penelitian ini adalah untuk mengetahui adanya tidak pengaruh metode Group To Group Exchange terhadap hasil belajar peserta didik pada materi perubahan lingkungan di salah satu SMA Islam di Medan. Penelitian ini merupakan penelitian quasi experiment dengan Nonequivalent pretest posttest control Group design. Analisis data hasil belajar peserta didik menggunakan rumus uji ttest, dengan bantuan pengolahan data SPSS versi 25. Analisis data hasil belajar peserta didik dengan hasil perhitungan rerata hasil belajar menunjukan kelas eksperimen yang menggunakan metode Group to Group Exchange lebih tinggi dari kelas kontrol. Uji prasyarat terbukti data berdistribusi normal dan homogen. Hasil perhitungan uji ttest diperoleh bahwa thitung lebih tinggi dari ttabel, maka ada pengaruh sehingga menunjukan thitung > ttabel maka Ha2 diterima. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh dan perbedaan sebelum dan sesudah penerapan metode Group to Group Exchange terhadap hasil belajar peserta didik pada materi perubahan lingkungan di salah satu SMA Islam di Medan. Sehingga temuan yang diperoleh, dapat diterapkan oleh guru dalam melaksanakan pembelajaran khususnya mata pelajaran biologi.